Gender research strategy - CGIAR Initiative on Sustainable Healthy Diets (International Food Policy Research Institute, 2023)
The primary goal of SHiFT’s gender-responsive food system research is to support the achievement of the SHiFT initiative’s objectives through greater attention to gender issues (Table 1). A secondary goal is to ensure that SHiFT research does not exacerbate existing inequalities, and, where feasible, fosters positive change in women’s empowerment. If SHiFT and its partners were to ignore gender issues, the interventions or other solutions that they design and test would likely fail to address the needs of specific groups where inequality persists.